Low nocturnal diastolic ocular perfusion pressure as a risk factor for NTG progression: a 5-year prospective study - Raman, Pushpa; Suliman, Nurull Bahya; Zahari, Mimiwati; Kook, Michael Scott; Ramli, Norlina Mohd (Springer Nature, 2018)
Objective: To assess the relationship between baseline intraocular pressure (IOP), blood pressure (BP) and ocular perfusion pressure (OPP), and the 5-year visual field progression in normal-tension glaucoma (NTG) patients. Design: Prospective, longitudinal study. Methods: Sixty-five NTG patients who were followed up for 5 years are included in this study. All the enrolled patients underwent baseline 24-h IOP and BP monitoring via 2-hourly measurements in their habitual position and were followed up for over 5 years with reliable VF tests. Modified Anderson criteria were used to assess VF progression. Univariable and multivariable analyses using Cox's proportional hazards model were used to identify the systemic and clinical risk factors that predict progression. Kaplan-Meier survival analyses were used to compare the time elapsed to confirmed VF progression in the presence or absence of each potential risk factor. Results: At 5-year follow-up, 35.4% of the enrolled patients demonstrated visual field progression. There were statistically significant differences in the mean diastolic blood pressure (p < 0.05) and diastolic OPP (p < 0.05) between the progressing and the non-progressing group. There was no association between IOP parameters and NTG progression. Multivariable analysis identified low nocturnal DOPP at baseline as a significant predictive risk factor for glaucomatous visual field progression at 5 years. An mmHg decrease in nocturnal DOPP increases the hazard of progression by 1.4 times. Patients with DOPP < 35 mmHg have 2.3-fold higher probability of progressing compared to the patients with DOPP > 43.7 mmHg (log rank = 0.018). Conclusion: Diastolic parameters of BP and OPP were significantly lower in the NTG patients who progressed after 5 years. Low nocturnal DOPP is an independent predictor of glaucomatous visual field progression in NTG patients.